Simplified model for hierarchical protein folding with self-consistent energy of contacts - Yesylevsky, S. O.; Kharkyanen, V. M. (Biophysical Bulletin, 2018)
Simplified protein folding model is considered. The protein is represented as a homopolymer, which is subject to hierarchical compactization. It is assumed that the first stage of folding is a formation of local first-level clusters, which later aggregate to form the clusters of higher hierarchical levels. Formation of the higher level clusters is assumed to be much slower than the dynamics of the lower-level cluster and is considered in adiabatic approximation. Formation of clusters cause the "freezing" of individual monomers, which lead to dramatic narrowing of the conformation space of the chain and to the steady motion toward the native energy minimum. The energy of contacts is considered to be dependent on the large-scale generalized structural coordinate, which determine the state of the folding chain. This coordinate, in turn, depends on the number of the formed contacts, which makes the system self-organized. It is shown that such a system can have two discrete steady states - unfolded and native. Probabilities of the states